IMPLEMENTASI FILSAFAT TRI HITA KARANA UNTUK KEBERLANJUTAN SUBAK ANGGABAYA SEBAGAI SUBAK LESTARI DI KOTA DENPASAR - Putu Udayani Wijayanti; Wayan Windia (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2021)
Subak is an autonomous organization that manages the irrigation system of an area of rice fields. This area has hydrological boundaries, a source of water, and a subak temple. Subak, which was recognizied by UNESCO as a world cultural heritage in 2012, implements the philosophy of Tri Hita Karana (THK). The sustainability of subak depends highly on how far this organization implements the THK. For this research, the area of Subak Anggabaya, located in Denpasar city, was chosen purposively as the research location because it is one of subak lestari (sustainable subak) in Denpasar. The data were collected from the informants who were chosen purposively because they know the implementation of the THK by Subak Anggabaya. This organization has been implementing THK components – Parhyangan, Pawongan, Palemahan – or in the concept of culture – Values, Social, Materials. The objective of this research is to identify which component of the THK is the most important one to the sustainability of Subak Anggabaya. The research found that the implementation of Parhyangan or values, particularly the implementation of awig-awig subak (subak regulations,) played the most important role in sustaining the existence of Subak Anggabaya as a subak lestari in Denpasar.